Tensile Test Of Fly-Ash-HDPE Hybrid Composite Via Finite Element Analysis - Intan Syaqirah, Mohd Zulkifli; Sharwinder Singh, Sukadevh Singh; Kugenrai, Shankar; Wong, Freddawati Rashiddy; Muhammad Izzat Nor, Ma'arof (INTI International University, 2020)
Fly-ash is one of the major wastes resulted from the power plant that generates electricity. In ensuring environmental sustainability, this waste should be properly disposed or utilized for other possible purposes. The goal of this study was to investigate the tensile strength of a newly developed fly-ash-high-density polyethylene (HDPE) hybrid composite via Finite Element Analysis (FEA) simulation. Four (4) types of hybrid composite were simulated in this study which were: (i) 100% HDPE with 0% fly-ash, (ii) 90% HDPE with 10% fly-ash, (iii) 80% HDPE with 20% fly-ash, and (iv) 70% HDPE with 30% fly-ash. The properties of the composite for four (4) different samples were obtained from the literature and via calculations. It was observed that the maximum stresses for samples 1, 2, 3 and 4 were 19.21MPa, 16.95MPa, 23.45MPa and 24.57MPa, respectively. The yield strengths were 26.1 MPa, 16.3 MPa, 22.5 MPa, and 23.7 MPa. It can be deduced that the tensile strength of the composite is increasing but the yielding strength is fluctuating. Furthermore, only sample 1 managed to record the factor of safety to be above 1.0. Non-homogeneity might be the cause of the values to fluctuate. For future studies, other types of mechanical properties assessment are recommended to be conducted on the fly-ash-HDPE hybrid composite.